The invention of Africa : gnosis, philosophy, and the order of knowledge - Mudimbe, V. Y. (Indiana University Press, 1988)
Looks at how European preconceptions have shaped Africa’s image. Western interpreters and African analysts have used categories and conceptual systems that depend on a Western epistemological order. (“Invention” is to be understood in the double sense of “discovery” and “fabrication.”) A highly influential work, but not easy reading.
free
Keywords: Théorie de la connaissance